O Programa Nacional de Alimentação Escolar (PNAE) no município de Pirapozinho (SP) - Aristides, Marleide de Jesus da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This work has as main objective to understand the features and operation of the National School Feeding Program (PNAE) in the municipality of Pirapozinho-SP, and investigate to what extent the program serves to improve the living conditions of local farmers, in other words, what is the relevance of this public policy for the permanence and social reproduction of farmers in rural space. Thus, we sought to understand how is the relationship of farmers with regard to the search for alternatives to the solution of common problems in the association of farmers, which allowed us to analyze the difficulties in the operationalization of the program in the county. Accordingly, we sought to also investigate what is the importance of the Program for the suppression of food insecurity in the municipality of Pirapozinho from the point of view of access to food by the school children. To achieve the proposed objectives resorted to basic bibliography pervading theme of research, as well as the survey of primary source data (interviews and questionnaires) and secondary (IBGE, SEADE, FNDE, CATI/LUPA). It was possible to ascertain with this work, that the operation of the Program in Pirapozinho follows the centralized management in the school lunch is prepared in the kitchen pilot, thus serving the schools. There is a low uptake of family farmers involved in the program, which reveals a character of selectivity, in which only four producers deliver their products to the PNAE. The lack of involvement and engagement of members (86) in relation to the inclusion in public policy is significant, resulting in poor coordination of farmers. It was also observed that the activity of the association is extremely utilitarian in order to meet the technical needs of its members. The Board of School Food ( CAE ) does not follow the ideal established by it, which is the participatory management of the Program, performing only annual meetings with it’s members. So, PNAE in ...

Este trabalho tem como principal objetivo compreender as características e o funcionamento do Programa Nacional de Alimentação Escolar (PNAE) no município de Pirapozinho/SP, e investigar em que medida o programa atende à melhoria das condições de vida dos agricultores familiares locais, ou seja, qual é a relevância dessa política pública para a permanência e a reprodução social dos produtores rurais no espaço rural. Com isso, buscou-se compreender como se dá a articulação dos agricultores familiares no que se refere à busca de alternativas para a solução de problemas comuns na associação de produtores rurais, o que permitiu analisar as dificuldades da operacionalização do programa no município. Nesse sentido, procurou-se também investigar qual é a importância do PNAE para a supressão da situação de insegurança alimentar no município de Pirapozinho, do ponto de vista do acesso à alimentação por parte das crianças em idade escolar. Para alcançar os objetivos propostos recorreu-se à bibliografia fundamental que permeia o tema da pesquisa, como também ao levantamento de dados de fonte primária (realização de entrevistas e questionários) e secundária (IBGE, SEADE, FNDE, CATI/LUPA). Foi possível verificar, com esse trabalho, que o funcionamento do PNAE em Pirapozinho segue a gestão centralizada, em que a merenda escolar é preparada na cozinha piloto, servindo assim às escolas. Há uma baixa adesão dos agricultores familiares envolvidos no programa, o que denuncia um caráter de seletividade, em que apenas quatro produtores entregam seus produtos para o PNAE. A falta de envolvimento e engajamento dos associados (86) em relação à inserção em políticas públicas é expressiva, resultando na baixa articulação dos agricultores. Foi observado também que a atuação da associação é extremamente utilitarista, a fim de corresponder às necessidades técnicas de seus associados ...
Keywords: Geografia; Agricultura familiar; Politicas publicas; Geography